Students’ Challenges and Language Learning Strategies In a Group Presentation In The Post-Pandemic Era - Wawan Setiawan (Universitas PGRI Semarang, 2023)
During the pandemic, online learning was the inevitable surge. Now, in the post-pandemic recovery, schools and universities have initiated to start offline learning. This research attempts to investigate challenges and students’ language learning strategies in giving a group presentation in the post-pandemic era. Fifty students, the third semester students taking Pre-Advanced Speaking class at STBA JIA Bekasi, participated in this research. The participants involved had online learning for the last two semesters and the third semester was their first time having offline classes. So, to address the research questions regarding their challenges and language learning strategies, the questionnaire was distributed. The findings showed that most of the students believed confidence was their major challenge in giving a group presentation in the post-pandemic era. While for the language learning strategies, the majority of participants adopted cognitive strategies such as planning and organizing their presentation.